1995
DOI: 10.1021/jm00010a024
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4''-Deoxy Motilides: Identification of a Potent and Orally Active Prokinetic Drug Candidate

Abstract: As an approach to discovering highly potent motilides with oral activity, novel 4"-deoxy derivatives of 8,9-anhydroerythromycin 6,9-hemiacetal were designed, synthesized, and evaluated for their gastrointestinal prokinetic activities. These compounds were orders of magnitude more potent than their 4"-hydroxy analogs in inducing smooth muscle contractions in an in vitro rabbit duodenal assay. Removal of the 12-hydroxy group, which was aimed at improving oral bioavailability, also afforded further potentiation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 8 publications
0
45
0
Order By: Relevance
“…The motility stimulating effect of ABT-229 in vitro was found to be much stronger than that of erythromycin and the oral bioavailability of this compound in dogs was found to be relatively high (39%). 21 Thus, the prokinetic effect of ABT-229 in vivo was expected to be considerably stronger than that of erythromycin. The doses of ABT-229 used in this study (4 and 16 mg) were much lower than the doses of erythromycin used in previous studies (40±350 mg).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motility stimulating effect of ABT-229 in vitro was found to be much stronger than that of erythromycin and the oral bioavailability of this compound in dogs was found to be relatively high (39%). 21 Thus, the prokinetic effect of ABT-229 in vivo was expected to be considerably stronger than that of erythromycin. The doses of ABT-229 used in this study (4 and 16 mg) were much lower than the doses of erythromycin used in previous studies (40±350 mg).…”
Section: Discussionmentioning
confidence: 99%
“…One of these, ABT-229 (8,9-anhydro-4¢¢-deoxy-3¢-N-desmethyl-3¢-N-ethylerythromycin B 6,9-hemiacetal), has a relatively high bioavailability after oral administration and strong prokinetic effects in vitro. 21 This study was designed to investigate the effects of two single oral doses (4 mg, 16 mg) of ABT-229 on the SUMMARY Background: ABT-229 is a recently developed derivative of erythromycin, devoid of antibiotic activity. We studied the effect of ABT-229 on gastric emptying and postprandial antroduodenal motility in healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…Erythromycin-A (EM-A), EM-A enol ether (ME4), N-ethyl, N-methyl EM-A (ME36), EM-B enol ether (ME67), and N-ethyl, N-methyl EM-A enol ether (EM-523) were obtained from Prof. J. Hoogmartens (Laboratory of Pharmaceutical Chemistry, University of Leuven, Belgium). N-Ethyl, N-methyl 4Љ deoxy EM-B enol ether (ABT-229) was a gift from Dr. P. Lartey (Lartey et al, 1995;Abbott Laboratories, Abbott Park, IL). Macrolide KOS1326 was synthesized by Kosan Biosciences, Inc. (Hayward, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Motilin Other names MTLR1 (Feighner et al, 1999), GPR38 (Mckee et al, 1997) Ensembl ID ENSG00000102539 Principal transduction G q/11 (Depoortere and Peeters, 1995;Feighner et al, 1999) Rank order of potency Motilin4ABT229, mitemcimal 4erythromycin (Clark et al, 1999) Selective agonists ABT229 (Lartey et al, 1995), mitemcinal (Koga et al, 1994;Takanashi et al, 2007) ]-NPS Polymorphisms in the NPS receptor have been suggested to be associated with asthma (Laitinen et al, 2004;Vendelin et al, 2005) and irritable bowel syndrome (D'Amato et al, 2007).…”
Section: Citation Informationmentioning
confidence: 99%